When does hepatitis B virus meet long-stranded noncoding RNAs? - Lei, Bingxin; Song, Hongxiao; Xu, Fengchao; Wei, Qi; Wang, Fei; Tan, Guangyun; Ma, Haichun (Frontiers in Microbiology, 2022)
Hepatitis B virus (HBV) infection in humans and its associated diseases are long-standing problems. HBV can produce a large number of non-self-molecules during its life cycle, which acts as targets for innate immune recognition and initiation. Among these, interferon and its large number of downstream interferon-stimulated gene molecules are important early antiviral factors. However, the development of an effective antiviral immune response is not simple and depends not only on the delicate regulation of the immune response but also on the various mechanisms of virus-related immune escape and immune tolerance. Therefore, despite there being a relatively well-established consensus on the major pathways of the antiviral response and their component molecules, the complete clearance of HBV remains a challenge in both basic and clinical research. Long noncoding RNAs (lncRNAs) are generally more than 200 bp in length and perform different functions in the RNA strand encoding the protein. As an important part of the IFN-inducible genes, Interferon stimulated-lncRNAs are involved in the regulation of several HBV infection-related pathways. This review traces the basic elements of such pathways and characterizes the various recent targets of lncRNAs, which not only complement the regulatory mechanisms of pathways related to chronic HBV infection, fibrosis, and cancer promotion but also serve as some possible new therapeutic targets for controlling HBV infection and the malignant transformation of hepatocytes.